2006
DOI: 10.1073/pnas.0601192103
|View full text |Cite
|
Sign up to set email alerts
|

Activation of FIP1L1-PDGFRα requires disruption of the juxtamembrane domain of PDGFRα and is FIP1L1-independent

Abstract: Genetic abnormalities that result in expression of chimeric tyrosine kinase proteins such as BCR-ABL1 and ETV6-PDGFR␤ are common causes of hematopoietic malignancies. The paradigm for constitutive activation of these fusion tyrosine kinases is enforced homodimerization by self-association domains present in the fusion partner proteins. The unique interstitial deletion on chromosome 4q12 that leads to expression of the FIP1L1-PDGFR␣ fusion tyrosine kinase was recently identified as a cause of chronic eosinophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(115 citation statements)
references
References 26 publications
(44 reference statements)
5
106
0
Order By: Relevance
“…We generated FLAG-tagged Altogether, these results indicate that the C-terminal portion of PDGFRA, by itself, possesses the ability to homodimerize and is a constitutively active kinase. These results are consistent with a previous report, describing that the FIP1L1 portion is dispensable for activation of FIP1L1-PDGFRA for its kinase activity [7].…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…We generated FLAG-tagged Altogether, these results indicate that the C-terminal portion of PDGFRA, by itself, possesses the ability to homodimerize and is a constitutively active kinase. These results are consistent with a previous report, describing that the FIP1L1 portion is dispensable for activation of FIP1L1-PDGFRA for its kinase activity [7].…”
Section: Resultssupporting
confidence: 94%
“…These results were consistent with previous reports, stating that the FIP1L1 portion is dispensable for the activation of FIP1L1-PDGFRA kinase activity [7]. The FIP1L1 portion is, however, a contributing factor to the higher proliferating activity, induced by FIP1L1-PDGFRA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we have observed that interruption of the juxtamembrane of PDGFRa is indispensable for kinase activation in the context of FIP1L1-PDGFRa. 58 Indeed, it was previously shown that mutations or duplications within the juxtamembrane region of the PDGFR family of tyrosine kinases can cause constitutive activation of their kinase activity. 59,60 Table 4 PDGFRB fusion genes in addition to ETV6-PDGFRB identified in patients with MPNs and eosinophilia a Not a chronic MPN, but diagnosed in a case of AML at relapse.…”
Section: Mechanism Of Activation Of the Fip1l1-pdgfra Tyrosine Kinasementioning
confidence: 99%